Efficacy of Cyproheptadine Monotherapy in Hepatocellular Carcinoma With Bone Metastasis: A Case Report - Feng, Yu-Min; Chen, Tsung-Hsien; Berman, Dara; Chou, Chu-Kuang; Liao, Kai-Sheng; Hsieh, Ming-Chih; Chen, Chi-Yi (Frontiers in Oncology, 2021)
Background: Hepatocellular carcinoma (HCC) is one of the most common causes of cancer-related deaths worldwide. Particularly, cases of bone metastasis have poorer prognoses. Case Presentation: A 62-year-old woman with suspected advanced HCC accompanied by bone metastasis with severe back pain and sciatica showed disease remission after cyproheptadine monotherapy. Initially, her serum alpha fetal protein (AFP) level was high, reaching up to 17697.62 ng/ml. A dose of 4 mg cyproheptadine, 3 times a day for 17 months was prescribed as the only treatment. Within 3 months, the serum AFP level gradually normalized down to 4.3 ng/ml. Both liver biopsy and bone biopsies were subsequently performed after 2 weeks of cyproheptadine. The results showed no malignancy. During the 34 months of follow-ups, the serum AFP remained normal in the range of [1.05 to 2.86] ng/ml. The patient has survived for 5 years without back pain and sciatica thus far. Conclusions: This is the first report to investigate a successful clinical approach in cyproheptadine monotherapy for an advanced HCC patient with bone metastasis. We recommend cyproheptadine as a potential anti-HCC agent for the treatment of HCC with bone metastasis, but more related studies such as prospectively clinical trials, and ideally randomized trials are still needed.